Modelling open channel flow - Hopton, Stephen (2010)
The study of open channel flow and dam breaking is not a new topic in computational fluid dynamics. However it has only recently started to gain significant attention from researchers using meshless methods, i.e. numerical modelling techniques which do not rely on the use of a mesh to discretise the domain. The research presented here is an attempt to use the meshless method known as smoothed particle hydrodynamics (SPH) to simulate the flow of water down a channel.